The roles of actors in the host society in the integration of inmigrants associations: a social networks analysis approach - Gaete Fiscella, José Manuel; Mena Martínez, Luis (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article explores the stages of integration of immigrant associations in Spain according to stock of social capital, specifically, given the relationships established with actors in the environment, and consequently this role is derived for each type of counterpart. The data are drawn from a representative sample consisting of 225 immigrant associations around the country. The results suggest that immigrant associations play cohesive and specific roles with their peers, even achieve certain asymmetries in their favor with certain actors in the host society. On the other hand, native actors host society are distributed in a continuum ranging from the development of specific roles to other multiple, and even contradictory, which, as a whole, ends up drawing a map of complex and diverse opportunities for integration of associations.
Keywords: social networks; associations; immigrants; integration; social capital